Characterization of auto-Ignition phenomena in spark ignition internal combustion engine using gaseous fuels obtained from biomass (2018)
Studies have been carried out on the phenomenon of auto-ignition in liquid fuels and natural gas, but research on the application of gaseous fuels obtained from biomass is limited. Existing investigations about autoignition mainly focused on the combustion kinetics to determine the delay time, but not on the prediction of the set of parameters that encourage the presence of the phenomenon. In the present research, a thermodynamic model is developed for the prediction of the auto-ignition in Spark Ignition Internal Combustion Engine operated with gaseous fuels, which are obtained from the process of gasification of biomass. The formulated model can handle variable compositions of gaseous fuels and to optimize the main operational parameters of the engine, to verify its influence on the phenomenon under study. Results show the application of this type of alternative fuels in commercial engines that operated with natural gas, varying engine operational parameters while maximizing the power output of the engine